Implementasi Metode Drill dalam Mengatasi Kesulitan Menghafal Kosakata Bahasa Arab di Madrasah Tsanawiyah - Radiatul Jannah; Sitti Hasnah; Atna Akhiryani (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2023)
The Research discusses the Implementation of the Drill Method in Overcoming the Difficulty of Memorizing Arabic Vocabulary at MTs Alkhairaat Pangi, Parigi Moutong Regency. With the following problem formulation: 1) How to implement the drill method in overcoming the difficulty of memorizing vocabulary in MTs Alkhairaat Pangi, Parigi Moutong Regency. 2) What are the inhibiting factors and supporting the implementation of the drill method in overcoming the difficulty of memorizing vocabulary in MTs Alkhairaat Pangi, Pangi, Parigi Moutong Regency. The results showed that the implementation of the drill method in overcoming the difficulty of memorizing vocabulary in Class VIII MTs Alkhairaat Pangi was carried out by the teacher by preparing 10 vocabulary words using image media that was pasted or written on the blackboard, after which the teacher and students practiced together repeatedly. Then the teacher evaluates the vocabulary that has been given to each student. The inhibiting factors are the lack of interest of students in learning Arabic and the lack of books that are used as references in learning Arabic. The supporting factors in memorizing students are school environment factors, the state of facilities and infrastructure, and support from parents. The implication of this research is for teachers to pay more attention to matters related to Arabic language learning, especially increasing learning reference books and always providing motivation to students so as not to get bored quickly in memorization. A lot or a little memorized vocabulary can improve students' mastery of Arabic vocabulary, so as to overcome the difficulties of students in memorizing Arabic vocabulary and make it easier for students to understand Arabic texts.